Laccase immobilization on magnetic nanoparticles modified with silica-gelatin hybrid - Lande, Evi Setiani (2023)
Laccases are applicable in numerous reactions as part of industrial significance, namely in polymer industry, bioremediation, biomass conversion and wine industry. However, industrial applications of laccases are limited due to their poor recyclability and difficulty to isolate from the reaction system, which results in high commercial costs. The main considerations of enzyme immobilization are compatibility, activity, and reusability. Thus, magnetic hybrid nanoparticles have been considered as one of promising materials for laccase immobilization support. Magnetic nanoparticles (MNPs) core afford facile magnetic separation process. Hybrid organic-inorganic shell creates mechanically tuneable material and provide hydroxyl and amino groups, enabling high-affinity interactions with enzymes. In this work, magnetic hybrid NPs modified with silica-gelatin-alkoxysilane were prepared employing versatile synthetic route and characterized by FTIR spectroscopy, elemental, TEM, and zeta potential analysis. Fe₃O₄@SiO₂/Gel-A/ICPTES exhibited the highest activity compared to other magnetic hybrid NPs, thus it was selected as a support material for laccase. Considering the recovered activity and recyclability, laccase immobilization on Fe₃O₄@SiO₂/Gel-A/ICPTES at pH 5 with 3 h of contact time using higher concentration of laccase was considered as the most feasible immobilization condition. The Michaelis-Menten kinetic parameters of laccase immobilized at the optimum conditions showed a Vₘₐₓ of 1.25 μmol.gˉ¹.minˉ¹ and a KM of 75.83 μM, which was approximately four times higher than free laccase. Immobilized laccase displayed a fair recyclability, with 54% of activities retained in the 5th cycle. However, the immobilization of laccase on Fe₃O₄@SiO₂/Gel-A/ICPTES generally displayed low immobilization yields (<20%). Therefore, further adjustments such as enzyme-to-material proportion and immobilization temperature are necessary.